2018
DOI: 10.1080/14729679.2018.1557059
|View full text |Cite
|
Sign up to set email alerts
|

Alumni perspectives on a boarding school outdoor education programme

Abstract: Experiences of outdoor education are believed to have significant impacts on participants, but research on the lasting influences of extended programmes is limited. Gordonstoun School, an independent residential school founded by Kurt Hahn in 1934, provides a rich legacy of outdoor education against which to explore any enduring outcomes. Drawing on data from an online survey (n=1174) and focus group interviews (n=50) with alumni from Gordonstoun, this research characterises the defining features of their out-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Intake 2 students did not record the same statistically significant deterioration in most motivation and engagement factors, however means trended in the same direction as Intake 1 showing an initial decrease after return to the normal school environment. Focus group comments indicated that students were able to internalize personal skills developed by Glengarry-specific experiences and could apply them to other environments, which is line with previous OAE research (e.g., Bobilya et al, 2015 ; Beames et al, 2020 ). In contrast, students’ sense of connection to school and learning seemed to be linked to the context they were in, and therefore changed once they returned to the main school environment.…”
Section: Discussionsupporting
confidence: 86%
“…Intake 2 students did not record the same statistically significant deterioration in most motivation and engagement factors, however means trended in the same direction as Intake 1 showing an initial decrease after return to the normal school environment. Focus group comments indicated that students were able to internalize personal skills developed by Glengarry-specific experiences and could apply them to other environments, which is line with previous OAE research (e.g., Bobilya et al, 2015 ; Beames et al, 2020 ). In contrast, students’ sense of connection to school and learning seemed to be linked to the context they were in, and therefore changed once they returned to the main school environment.…”
Section: Discussionsupporting
confidence: 86%
“…The outcomes of the expedition experiences generally align with the four categories used by Stott et al with the most salient outcome being learning about self. However, most of the reviewed studies have a handful of participants with a retrospection of more than 20 years, confirming the limited amount of research about the long-term influence of expeditions (Allison et al, 2018; Allison & Von Wald, 2013; Beames et al, 2020; Ewert & McAvoy, 2000; Gartner-Manzon & Giles, 2018; Gassner, 2006; Houge Mackenzie et al, 2014). The extant literature is also from a range of mixed cultural contexts (countries ranging from Canada, USA, UK, Japan), cultural traditions of expeditions for different purposes and a wide range of types of outdoor experiences (for example more or less wilderness, water based, land based).…”
Section: Literature Reviewmentioning
confidence: 82%
“…To understand the long-term influence of expeditions, a retrospective research design was chosen. Retrospective studies have the advantage of studying impacts over long periods, including participants of different ages (Kellert & Derr, 1998) as well as to illuminate outcomes (Beames et al, 2020). Further, it has been argued that retrospective studies are more reliable than studies using questionnaires given just after the expedition experience participants may be experiencing post-group euphoria (Hattie et al, 1997;Scrutton & Beames, 2015).…”
Section: Retrospective Studymentioning
confidence: 99%
“…Positivism can expose causal relationships in OEE, but cannot fully capture the complexity of experience, learning, and growth when learning outside? Recent work that has employed a positivist 'average effect' causal approach in outdoor learning (e.g., Beames et al, 2018;Cooley et al, 2020;Scrutton, 2020) suggests this view is too simple an answer. Quibell et al (2017) somewhat alleviate this causal tension by outlining why the unitary view on exposing causal relationships is important in outdoor learning.…”
Section: A Rejoinder: Confusion Complexity or Causation?mentioning
confidence: 99%